2005
DOI: 10.1111/j.1365-2672.2005.02556.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a bacteriocin produced by Enterococcus faecium GM-1 isolated from an infant

Abstract: Aim: To partially characterize the bacteriocin produced by the GM-1 strain of Enterococcus faecium, isolated from the faeces of a newborn human infant. Methods and Results: The bacteriocin produced by E. faecium GM-1 showed a broad spectrum of activity against indicator strains of Escherichia coli, Staphylococcus aureus, Vibrio spp., Salmonella typhimurium, Listeria monocytogenes, Lactobacillus acidophilus, and Streptococcus thermophilus. Treatment of the GM-1 bacteriocin with proteolytic enzymes reduced its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 19 publications
3
58
1
3
Order By: Relevance
“…faecalis strains from dairy products and/or silage displaying antibacterial activity have been isolated [20][21][22]. Isolation of bacteriocinogenic enterococci from faeces of human and animal have also been well reported [23][24][25]. Our fi ndings are in agreement with these studies showing that bacteriocin producing enterococci can be found associated with gastrointestinal tract of human.…”
Section: Discussionsupporting
confidence: 83%
“…faecalis strains from dairy products and/or silage displaying antibacterial activity have been isolated [20][21][22]. Isolation of bacteriocinogenic enterococci from faeces of human and animal have also been well reported [23][24][25]. Our fi ndings are in agreement with these studies showing that bacteriocin producing enterococci can be found associated with gastrointestinal tract of human.…”
Section: Discussionsupporting
confidence: 83%
“…Each enzyme was dissolved in sterile demineralised water and added to the CFNS to the final concentration of 1.0 mg/ml. Following incubation, at 37°C for 2 h, the reaction mixtures were heated to 100°C for 10 min to inactivate the enzymes before assessing the remaining bacteriocin activity against selected indicator strains (Kang & Lee 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Enterococcal bacteriocins, often termed enterocins, have been widely investigated, mainly because they are active against gram-positive food-borne pathogens, such as Listeria monocytogenes, Staphylococcus aureus, and Bacillus cereus. The vast majority of enterocins are active only against gram-positive bacteria (10, 17); however, some exceptions with broad activity spectra described in recent years showed the ability to inhibit the growth of gram-negative microorganisms (5,11,13).…”
mentioning
confidence: 99%
“…Enterococcal bacteriocins, often termed enterocins, have been widely investigated, mainly because they are active against gram-positive food-borne pathogens, such as Listeria monocytogenes, Staphylococcus aureus, and Bacillus cereus. The vast majority of enterocins are active only against gram-positive bacteria (10, 17); however, some exceptions with broad activity spectra described in recent years showed the ability to inhibit the growth of gram-negative microorganisms (5,11,13).The increasing number of enterocins reported in the literature and the emergence of novel structures that could not be included in classical bacteriocin classifications (12,14,17) prompted the grouping of enterocins into a new four-class scheme by Franz et al (8). Most enterocins known so far were included in class II (small, nonlantibiotic peptides), which was divided into three subgroups: class II.1, enterocins of the pediocin family; class II.2, enterocins synthesized without a leader peptide; and class II.3, other linear, non-pediocin-like enterocins.…”
mentioning
confidence: 99%